Internal Communication in Corporate Identity of Public Health Workers in Lima Region - Ostos Cueva, Efraín (2016)
The main aim of this research was to determine the relation that exists between the internal communication as tool of Public Relations and the corporate identity of Public Health workers at Lima Region. It’s a non-experimental study with a correlational level. The sample was integrated by 224 employees. The research demonstrates (by means of the coefficient of Spearman’s correlation) that there is not a significant relation between internal communication and corporate identity in Public Health workers at Lima. Also, there is a weak relation between research variables.